The Association Between Urinary Tract Stones and The Incidence of Urinary Tract Infections - Budaya, Taufiq Nur; Rohman, Mohammad Saifur; Ardhino, Ardhino; Dhani, Fauzan Kurniawan (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2024)
Introduction. This research was conducted to investigate the association between urinary tract stones and the occurrence of urinary tract infections in patients receiving treatment at Saiful Anwar General Hospital in Malang.Methods. This research constitutes an analytical observational study employing a case-control research design conducted at Saiful Anwar General Hospital in Malang from 2015 to 2020.Results. This study comprised a sample size of 104 patients. In the group of patients with urinary tract stones, the highest occurrence was among men (77.3%), particularly those aged between 30-60 years (59.1%). In the group of patients with UTIs, males had the highest prevalence (67.3%), with a significant portion at the age of 50 (55.8%). The Chi-Square analysis investigating the association between urinary tract stones and the presence of urinary tract infections resulted in a p-value of 0.008, accompanied by an Odd Ratio of 4.566.Conclusions. A notable association has been identified between urinary tract stones and the presence of urinary tract infections.